Abuse of internet for terrorist purposes - Zirojević-Fatić Mina (Međunarodni Problemi)
In this analysis, the author tried to establish a relationship, similarities and differences between the expression of terrorist organizations on the Internet and in conventional media. It is particularly important that the terrorists use the Internet as a weapon, as a means of communication and among activists as a conventional medium. The paper analyzed only the third way - use the Internet as a conventional media.